If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 25 = 12x + -10 Reorder the terms: 25 + 2x = 12x + -10 Reorder the terms: 25 + 2x = -10 + 12x Solving 25 + 2x = -10 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 25 + 2x + -12x = -10 + 12x + -12x Combine like terms: 2x + -12x = -10x 25 + -10x = -10 + 12x + -12x Combine like terms: 12x + -12x = 0 25 + -10x = -10 + 0 25 + -10x = -10 Add '-25' to each side of the equation. 25 + -25 + -10x = -10 + -25 Combine like terms: 25 + -25 = 0 0 + -10x = -10 + -25 -10x = -10 + -25 Combine like terms: -10 + -25 = -35 -10x = -35 Divide each side by '-10'. x = 3.5 Simplifying x = 3.5
| -81=g-9 | | 4b^2-90=-2b | | 34y+237= | | 3y-5+2(y-5)=15+8y | | 1/2x-3(x-5)=5(x-9) | | 8(n-5)=-16 | | y-9=-1(x-0) | | x-4+2x+5=91 | | f/12 | | 1/3x-3(x-5)=5(x-9) | | 4-7x/2-2=x/8 | | A=2(6)(9)+2(10)(9)+(6)(10) | | (4x+9)+(3x-2)=28 | | 2s+3(5-2s)=47 | | 3x-(x-5)+6=x+9 | | 3n+16=4n+24 | | (6x+3)+(x+16)=180 | | Y=5(x+2)-2 | | 7.5+2.5x= | | 2x-9(x+8)=x+1 | | X+2x+4x=133 | | 2x-(8x+5)=8x-19 | | 3(x-2)-1=2 | | (X+7)2+20=0 | | 9x-15=6x+6 | | -6(x-3)=-2x+2 | | g/-912 | | D=125 | | (X+3)2-4=20 | | 4z+1-s=1+z | | 9x-15=6n+6 | | 5x+(x+96)=180 |